2016
DOI: 10.1016/j.bbmt.2016.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Pharmacokinetics-Directed Busulfan, Cyclophosphamide, and Etoposide Conditioning and Autologous Stem Cell Transplantation for Lymphoma: Comparison of a Multicenter Phase II Study and CIBMTR Outcomes

Abstract: Busulfan, cyclophosphamide and etoposide (BuCyE) is a commonly used conditioning regimen for autologous stem-cell transplantation (ASCT). This multicenter, phase 2 study examined the safety and efficacy of BuCyE with individually-adjusted busulfan based on pre-conditioning pharmacokinetics. The study initially enrolled Hodgkin lymphoma (HL) and non-Hodgkin lymphoma (NHL) patients 18–80 years, but was amended due to high early treatment-related mortality (TRM) in patients >65 years. BuCyE outcomes were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Notably, BU TDM has not been consistently used in BuCyE conditioning for autologous HCT. Most publications show that weight-based BU dosing without BU TDM was used [54], although BU TDM can be used [70,73]. In patients with non-Hodgkin's lymphoma receiving BuCyE, improved OS with i.v.…”
Section: Faq4: Is Oral or Intravenous Bu Preferred? IV Bu Tends To mentioning
confidence: 99%
“…Notably, BU TDM has not been consistently used in BuCyE conditioning for autologous HCT. Most publications show that weight-based BU dosing without BU TDM was used [54], although BU TDM can be used [70,73]. In patients with non-Hodgkin's lymphoma receiving BuCyE, improved OS with i.v.…”
Section: Faq4: Is Oral or Intravenous Bu Preferred? IV Bu Tends To mentioning
confidence: 99%
“…With the aim of obtaining a higher anti-lymphoma activity and/or reducing the toxic effects, a number of studies suggested the possibility of improving the outcomes of NHL patients through modifying the conditioning regimens 8 10 . BuCyE (busulfan, cyclophosphamide, and etoposide) 11 , 12 and Benda-EAM (bendamustine, etoposide, cytarabine, and melphalan) 13 , 14 were approved to be effective and safe for NHL patients 15 , 16 . However, idarubicin, which was a widely used anthracycline drug for NHL patients, was rarely reported to be added in conditioning regimen.…”
Section: Introductionmentioning
confidence: 99%
“…The two Phase III prospective randomized studies that established the role of ASCT in such patients used BEAM conditioning, 106 , 107 which remains one of the most commonly used regimens to date. Other common regimens include cyclo-phosphamide, carmustine and etoposide (CBV) with various dosing modifications 121 125 ; busulfan-based regimens such as busulfan and cyclophosphamide (BuCy), 126 busulfan and melphalan (BuMel), 127 busulfan, etoposide and cyclophosphamide (BuCyE) 128 , 129 a or triple alkylator regimen of busulfan, melphalan and thiotepa (BuMelTt). 130 , 131 total body irradiation (TBI) (or total lymphoid irradiation [TLI])-based regimens have also been used as conditioning regimens in previously nonirradiated patients 8 , 113 , 123 , 132 , 133 ; however, there has been a swift away from such regimens over time due to concerns for increased associated risk of secondary malignancies and long-term toxicity.…”
Section: Transplantation Strategies For Refractory or Relapsed Hlmentioning
confidence: 99%